2009
DOI: 10.1128/aac.01452-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Ceftaroline Alone and in Combination against Clinical Isolates of Resistant Gram-Negative Pathogens, Including β-Lactamase-Producing Enterobacteriaceae and Pseudomonas aeruginosa

Abstract: Ceftaroline is a novel broad-spectrum cephalosporin that exhibits bactericidal activity against many grampositive and -negative pathogens. However, the activity of ceftaroline cannot be solely relied upon for eradication of multidrug-resistant gram-negative isolates, such as Pseudomonas aeruginosa and extended-spectrum ␤-lactamase (ESBL)-producing Enterobacteriaceae, which represent a current clinical concern. As drug combinations might be beneficial by potential synergy, we evaluated the in vitro activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Enhancement of activity was defined as an increase in kill of Ն2-log 10 CFU/ml by the combination of antimicrobials versus the most active single agent of that combination. Improvement was defined as a 1-to 2-log 10 CFU/ml increase in kill compared to the most active single agent, while combinations that result in a Ն1-log 10 CFU/ml bacterial growth compared to the least active single agent were considered antagonistic (32,33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancement of activity was defined as an increase in kill of Ն2-log 10 CFU/ml by the combination of antimicrobials versus the most active single agent of that combination. Improvement was defined as a 1-to 2-log 10 CFU/ml increase in kill compared to the most active single agent, while combinations that result in a Ն1-log 10 CFU/ml bacterial growth compared to the least active single agent were considered antagonistic (32,33).…”
Section: Methodsmentioning
confidence: 99%
“…Samples from each model were collected at 0, 4,8,24,32,48,56, and 72 h and diluted in 0.9% saline. Colony counts were determined by spiral plating appropriate dilutions using an automatic spiral plater (WASP; DW Scientific, West Yorkshire, England) to enumerate CFU/ml and avoid antibiotic carryover.…”
Section: Methodsmentioning
confidence: 99%
“…Time-kill curves were constructed by plotting the mean colony counts on a logarithmic scale versus the time with a lower limit detection of 2 log 10 CFU/ml. According to the 2009 guidelines of Antimicrobial Agents and Chemotherapy, synergy was defined as a Ն2-log 10 -unit decrease (100-fold drop) in the numbers of CFU per ml achieved with the combination and with the most efficient agent used alone at 24 h. Indifference and antagonism were defined as Ϯ1-to Ͻ2-log 10 -unit killing at 24 h compared to the activity of the most efficient agent alone and Ͼ1 log 10 unit of growth at 24 h compared with the activity of the least active agent, respectively (31). The bactericidal activities of the drugs alone and the drug combinations were defined as a reduction of Ն3 log 10 CFU/ml (99.9%) compared to the starting inoculum and to the most active antimicrobial agent at 24 h, respectively (15).…”
mentioning
confidence: 99%
“…To account for the potential breakdown of antibiotics in broth, bacterial cells grown in each tube were spun down and resuspended in fresh drug-containing broth at 24 and 48 h. Additionally, at 36, 48, and 72 h of incubation, culture aliquots of 100 l were taken from each tube and the drug carryover was minimized by dilution in MHB, as described above. Bacterial counts were determined by plating 100 l of the appropriate dilutions on duplicate Mueller-Hinton agar (MHA) plates and overnight incubation under ambient conditions at 37°C to enumerate the numbers of CFU/ml (16,31). Time-kill curves were constructed by plotting the mean colony counts on a logarithmic scale versus the time with a lower limit detection of 2 log 10 CFU/ml.…”
mentioning
confidence: 99%
“…Similar to cefotaxime in single-step experiments, in multistep procedures it selected ESBL variants of TEM [36]. Another study showed that ceftaroline was synergistic with the β-lactamase inhibitor, tazobactam, (up to 500-fold) against MDR Gram-negative pathogens such as ESBL-producing E. coli and K. pneumoniae [37]. Despite being active against resistant Gram-positive bacteria, ceftaroline was less active than currently used antimicrobial agents against Gram-negatives.…”
Section: Ceftarolinementioning
confidence: 99%